Effect of different types of activated carbon on the adsorption- reduction of Cr(Ⅵ) by mZVI/activated carbon - WANG Wenhao; CHENG Yexing; WANG Yuyin; HOU Tingting; WU Xiaofeng; LI Yucai (Gongye shui chuli)
Based on the excellent adsorption performance of activated carbon(AC) and its characteristic of forming a microelectrolysis system with micro zero-valent iron(mZVI), various mZVI/ACs composite materials were synthesized by ball milling(BM) method, and the removal efficiencies of Cr(Ⅵ) by these materials were explored. The mechanism of the optimal composite material for Cr(Ⅵ) removal was analyzed. The results indicated that BM could effectively combine AC with mZVI, and mZVI/AC(wood) had a better removal effect on Cr(Ⅵ) under short-term ball milling conditions. Cr(Ⅵ) in the solution was mainly reduced by secondary Fe2+, and AC not only enhanced the adsorption of Cr(Ⅵ) by mZVI/AC, but also promoted the corrosion of mZVI, thereby enhancing the removal of Cr(Ⅵ). By monitoring the concentration changes of Cr(Ⅵ) and total Cr, and combining with solid-phase XPS analysis, it was speculated that the potential removal pathways of Cr(Ⅵ) by mZVI/AC(wood) involved adsorption-reduction process and reduction-chelation-precipitation process.